O duelo dos pastores: um estudo sobre a figuratividade nas Bucólicas de Virgílio - Arantes, Caroline Talge [UNESP] (2015)
The expressive resources adopted by Virgil (70 - 19 a.C.), the celebrated poet from the time of Emperor Augustus, in his composition entitled Bucólicas are undoubtedly factors that contribute to the recognition of the author in the history of Latin Literature. The objective of this research is to identify such arrangements and analyze the textual mechanisms that constitute meaning and how they can be mobilized in the discursive production. When applying the principles of Literary Semiotics and Poetic, it is possible to investigate the selection and combination of the figurative elements present in the poems III, V and VII of Virgil's work, which are responsible for creating the concrete universe, representative of his specific thematic significance (the idealized world of shepherds and their relationship with nature, music and poetry). By highlighting the elements that classify the text as poetic of bucolic gender, this study intends to investigate the figurativity in classical latin texts based on the analysis of the effects of meaning. Therefore, with the theoretical framework based primarily on semiotic theory of meaning, proposed by A. J. Greimas, the research works on investigating how the figures installed in speech are combined and coated with expressiveness